2009
DOI: 10.1002/jhm.390
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hospital glycemic control at US Academic Medical Centers

Abstract: OBJECTIVE:To evaluate contemporary hospital glycemic management in US academic medical centers.DESIGN: This retrospective cohort study was conducted on patients discharged from 37 academic medical centers between July 1 and September 30, 2004; 1,718 eligible adult patients met at least 1 of the inclusion criteria: 2 consecutive blood glucose readings >180 mg/dL within 24 hours, or insulin treatment at any time during hospitalization. We assessed 3 consecutive measurement days of glucose values, glycemic therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 38 publications
0
32
0
1
Order By: Relevance
“…Another barrier to effective glycemic control may be concerns about insulin administration. Among 37 academic medical centers, recommended regimens of insulin therapy were prescribed in only 45% of patients, 44 and patients with hyperglycemia without a diagnosis of diabetes were less likely to be treated with insulin. 22 We found that 26% of patients with hyperglycemia on the DOS (46% of these being nondiabetic) did not receive insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Another barrier to effective glycemic control may be concerns about insulin administration. Among 37 academic medical centers, recommended regimens of insulin therapy were prescribed in only 45% of patients, 44 and patients with hyperglycemia without a diagnosis of diabetes were less likely to be treated with insulin. 22 We found that 26% of patients with hyperglycemia on the DOS (46% of these being nondiabetic) did not receive insulin.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Reports on the status of inpatient glucose control in large samples of hospitals are now available. 10,11 Glucose control is by no means the only component of inpatient hyperglycemia care in need of attention.…”
Section: Introductionmentioning
confidence: 99%
“…14 mic control with the use of basal insulin, which was attributed to "underdosing" basal insulin or lack of adequate prandial insulin coverage, lack of effective titration in response to hyperglycemia, and variation in the ordering and administration of basal insulin at different hospital sites. 23,24 According to The Endocrine Society's clinical practice guidelines for management of hyperglycemia in the noncritical care setting, checking HbA 1c levels in all inpatients with known diabetes or with hyperglycemia (random blood glucose level . 140 mg/dL) is recommended if this has not been done in the preceding 8 to 12 weeks.…”
Section: Glycemic Control In Non-critical Care Settingsmentioning
confidence: 99%